Parallels of the Development of Tax Law in Slovakia - Babčák, Vladimír (Challenges of Contemporary Tax Law: Jubilee Book Dedicated to Professor Włodzimierz Nykiel. Volume II, 2024)
The author presents a short historical look at the development of tax law in Slovakia after November 1989. The main focus of the article concerns questions about the status of tax law in the legal order and the distinct periods of its development. The discussion of this topic is related to the different time periods that form the circumstances of development of tax law within Slovak legal order. In the conclusions, the author points out the major challenges for the legislation and academic study of tax law that have been caused by globalization, Europeanisation, and the global pandemic.